2013
DOI: 10.1007/s00181-013-0762-x
|View full text |Cite
|
Sign up to set email alerts
|

Productivity in the euro area: any evidence of convergence?

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
52
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(58 citation statements)
references
References 54 publications
(28 reference statements)
6
52
0
Order By: Relevance
“…In these studies, macroeconomic and institutional factors, trade openness and policies that enhance the quality of human and capital stock are commonly found to play an important role in raising productivity growth (Barro, 2001;European Commission, 2014). For instance, a number of studies find that a skilled workforce tend to promote innovation, which, in turn, raises productivity (Sondermann, 2012). Similarly, investment in information and communication technology (ICT) and on R&D is commonly found to play a crucial role in explaining productivity performance (Griffith et al, 2004).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In these studies, macroeconomic and institutional factors, trade openness and policies that enhance the quality of human and capital stock are commonly found to play an important role in raising productivity growth (Barro, 2001;European Commission, 2014). For instance, a number of studies find that a skilled workforce tend to promote innovation, which, in turn, raises productivity (Sondermann, 2012). Similarly, investment in information and communication technology (ICT) and on R&D is commonly found to play a crucial role in explaining productivity performance (Griffith et al, 2004).…”
Section: Literature Reviewmentioning
confidence: 99%
“…As for the old EU Member States, Färe et al (2006) found that they do not form a single convergence club, while Kutan and Yigit (2007) showed that convergence is relevant only in some countries. Sondermann's (2014) results did not show convergence at the aggregate level, but the hypothesis of convergence was accepted for some service sectors and manufacturing sub-industries. For the CEE countries, Bijsterbosch and Kolasa (2010) found a strong productivity convergence both at the country and at the industry level.…”
Section: Introductionmentioning
confidence: 61%
“…To compare the level of productivity within CEE countries, the value added was transformed into a single currency unit taking into account price-level differences in the Euro area using purchasing power parities (PPPs). Current PPPs were chosen because they are more suitable for our data time interval (17-20 years) and because of long-run analysis drawbacks of constant PPPs (Sondermann, 2014).…”
Section: Datamentioning
confidence: 99%
“…Convergence analysis of India by Kumar and Managi (2012) and convergence analysis of the pulp and paper industries of OECD countries between 1991 and 2000 by Hseu and Shang (2005) together with Sondermann (2014), (Margaritis (2007), Kumar and Russell (2002), Maudos et al (2000), and the approach that the productivity growth accounting approach to the ranking of developing and developed nations by Raab and Feroz (2007) are several studies covering the same subject. There are some studies that investigate convergence on an industrial basis.…”
Section: Berj (8) 1 2017mentioning
confidence: 99%